Proper Resourcing (Staff and Equipment) - Reifer, Donald J. (Software Maintenance Success Recipes, 2011)
Proper resourcing is the next recipe for success. e world of soware development has many production-grade methods, models, and heuristics for estimating the time and e¥ort required to develop a soware product. Good books, articles, and papers abound that discuss this subject.1-3 e topic is considered important because these estimates are the basis of the budgets that are provided for soware product development. When estimates are short and teams are pressed to perform to inadequate budgets, teams try to achieve the impossible by embracing what some have called death marches and death spirals.4 When I look at the literature, it is apparent that more projects have failed because of impossible schedules and inadequate budgets than for all other reasons combined.